PTH-013 Is polyp detection rate altered by the number of procedures performed during a bowel scope screening list?. (22nd June 2015) - Warburton, R; Meagher, U; Tighe, R
Abstract : Introduction: A one-off screening flexible sigmoidoscopy at the age of 55 has been shown to significantly decrease incidence and mortality from bowel cancer. 1 As a result "bowel scope" screening was offered in 6 pilot centres from March 2013 and is now beginning to be rolled out nationwide. The delivery of this service varies between sites with no consensus on the optimum number of procedures per lists. At the Norfolk and Norwich University Hospital 2 rooms run simultaneously with initially 12 patients per endoscopist scheduled based on a turn around time of 20 mins. Due to a higher than expected polypectomy rates this was reduced to 10 in order to complete sessions in time. 23 patients are currently invited to a 2 room session in order to achieve an attendance of 10 patients per room. This has resulted in a wide variation in the number of people attending a bowel scope list. If more patients attend then there is the possibility that polyp detection rates may fall due to added pressure to complete the endoscopy in a set time, endoscopist fatigue and distance of bowel examined. The aim of this study is to detect any differences in polyp detection rates if 10 or more endoscopies are performed in an evening session. Method: Bowel Scope screening lists performed between 1st January 2015 and the 14th February 2015 at the Norfolk and Norwich University Hospital were retrospectively analysed. The number of procedures per list and polyp detection rates were recorded. Endoscopies were performed by 8 accredited bowel scope endoscopists under gold standard conditions. A student's T-test was used to test for difference in polyp detection rates between lists with 10 or more endoscopies and those with less than 10. Results: A total of 87 endoscopy lists were performed. 40 of these had 10 or morw procedures per list, 47 had 9 or less. The average number of procedures per list in each group was 10.5 and 8.2 respectively. The polyp detection rate in the 10 or more group was 17.8% whilst in the 9 or fewer groups is was 23.3% ( p value 0.035). Conclusion: There is a significant fall in the polyp detection rate if more than 10 endoscopies are performed in a single session, meaning some lesions are being missed. This finding could be important for new centres planning bowel scope screening especially as trusts are considering up to 12 procedures per list or all day bowel scope sessions. Disclosure of interest: None Declared. Reference: Atkin WS et al . Once-only flexible sigmoidoscopy in prevention of colorectal cancer: a multi-centre randomised controlled trial. Lancet . 2010 May 8;375(9726):1624–33